Analysis of the Commercial Bank Performance in Indonesia and China - Meng, Wang Jin; Ugut, Gracia S (KINERJA, 2022)
The purpose of this study is to compare the impact of capital structure on commercial banks' performance in Indonesia and China. The study chose 13 commercial banks from Indonesia and 12 banks from China for the period of 5 years, from 2015 to 2019. The study deployed a data panel regression analysis to analyze the secondary data that was obtained from the financial statements of these commercial banks. In this study, ROA and ROE are the measures used for Bank Performance. Four dependent variables: loan to deposit ratio, debt to asset ratio, capital adequacy and asset size are the independent variables. The results showed that LTD, AS and DTA have positive significant influences on ROA, while DTA and CAR have positive significant relationship on ROE in the study of Indonesian banks. Only AS have negative significant impact on both ROA and ROE, DTA and CAR have positive significant impact on ROA, while LTD has significant relationship on ROE in the study of commercial banks in China.